2006
DOI: 10.1037/1053-0797.16.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the good fortune scale: A new tool for the study of "big dreams."

Abstract: This article proposes a revision of the good fortune (GF) scale of the Hall and Van de Castle (HVDC;1966) content analysis scoring system. In place of the original one-point GF scale, this proposed revision offers a 6-point scale that conceptually matches the HVDC system's 6 types of misfortune. The GF scale is then applied to the 1000 HVDC norm dreams to generate a new estimation of the average frequency of the 6 types of good fortune. These findings are discussed in relation to the study of highly memorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The first hypothesis was supported by our data (see Tables 1 and 2), showing that the most memorable dreams did indeed have much higher scores for CI intensity. This confirms previous smaller studies showing the same result (Hartmann, 2008;Hartmann & Kunzendorf, 2005-2006. As shown in Table 1, the effect size was in the same range as in the previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The first hypothesis was supported by our data (see Tables 1 and 2), showing that the most memorable dreams did indeed have much higher scores for CI intensity. This confirms previous smaller studies showing the same result (Hartmann, 2008;Hartmann & Kunzendorf, 2005-2006. As shown in Table 1, the effect size was in the same range as in the previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…CI intensity has turned out to be a very useful measure. Interrater reliability has been high: r ϭ .70 to .90 in a variety of studies (Hartmann & Kunzendorf, 2005-2006Hartmann, Kunzendorf, Rosen, & Grace, 2001;Hartmann, Zborowski, Rose, & Grace, 2001). In a series of controlled studies, CI intensity has been found to be increased after trauma and in students reporting abuse at any time (Hartmann, Zborowski, Rose, & Grace, 2001).…”
Section: Central Image Intensity Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…276-77 and Jung 1945/1948. Systematic research has described features to identify such dreams (Kluger 1955), (Bulkeley 2006).…”
Section: Core Quality 10: Dreams Are Psychological Energy Landscapesmentioning
confidence: 99%
“…Hsu and Yu Good Fortune Scale. Bulkeley's (2006) GF Scale was utilized in this study to capture the presence of positive experiences. It was created as a revision of Hall and Van de Castle's (1966) original scale, which only has a single coding for all good fortunes, as opposed to six for misfortunes.…”
mentioning
confidence: 99%